Amyopathic dermatomyositis with a rapidly progressing interstitial pneumonia - Darija Logvinova; Dace Žentiņa; Kristīne Ivanova; Inita Buliņa; Zaiga Kravale (European Journal of Case Reports in Internal Medicine)
Background: Clinically amyopathic dermatomyositis (CADM) is a rare subtype of idiopathic inflammatory myositis often linked with the presence of autoantibodies targeting melanoma differentiation-associated protein 5 (MDA5). Patients with CADM are at increased risk of developing rapidly progressing interstitial lung disease, which significantly increases both morbidity and mortality compared to other forms of inflammatory myopathies. While there is no standardized treatment regimen, current therapeutic strategies are generally focused on combination immunosuppressive therapies. Despite early diagnosis and immunosuppressive therapy, the disease remains highly aggressive and is associated with a poor prognosis. Case report: This report describes the case of a 63-year-old previously healthy male who developed acute interstitial pneumonia. Polymerase chain reaction testing for pneumonia pathogens and routine autoimmune antibody screening were both negative. Despite treatment with corticosteroids and broad-spectrum antibiotics, the patient’s condition continued to deteriorate. A multidisciplinary team was assembled, and a myositis antibody panel was ordered, which led to the diagnosis of anti-MDA5 associated clinically amyopathic dermatomyositis. The patient was initiated on treatment with cyclophosphamide, intravenous immunoglobulin, and a calcineurin inhibitor. However, his condition remained critical, and he ultimately succumbed to respiratory failure. Conclusion: In all cases of rapidly progressive interstitial pneumonia of unclear aetiology, anti-MDA5-associated interstitial lung disease should be considered, regardless of the presence or absence of extrapulmonary manifestations. Despite early recognition and aggressive immunosuppressive therapy, patients with anti-MDA5-associated rapidly progressive interstitial lung disease face a mortality risk of up to 80%. A multidisciplinary approach, with collaboration between specialized centres, is crucial for early diagnosis and timely initiation of treatment.